STUDI ANALISIS KEMITRAAN ORANG TUA DAN SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN SISWA - Akhyar, Muaddyl; Batubara, Juliana; Deliani, Nurfarida (FIKRAH, 2024)
The case of the teacher who dared to reprimand a student for smoking is a clear example of how the partnership between parents and schools can be a decisive factor in overcoming problems that arise in the world of education. This incident illustrates the role of parents who are active in supporting their children’s educational process, as well as schools that are committed to character building and student discipline. The purpose of this study is to explain the Urgency of Parent and School Partnerships in Improving Student Discipline (Case Study of Teacher Reprimanded by Parents for Reprimanding Smoking Students). The method used in this study uses a qualitative method with a case study approach. The case study approach is a powerful tool for exploring a particular situation or event carefully, deeply, and in detail. This approach allows researchers to gain a better understanding of the complexity and dynamics of a phenomenon or problem in a real context. The results of this study indicate that the Urgency of Parent and School Partnerships in Improving Student Discipline. These partnerships have a significant impact in shaping student character and creating an effective educational environment are Strengthening Values and Discipline, Holistic Approach to Education, Open and Constructive Communication, Key Support in Rule Implementation, Improved Academic Performance, Better Monitoring and Support, Reducing Rule Breaking, Teaching Cooperation and Responsibility.